Analysis Of Peace Education In The Implementation Of The Peace Village Program Reviewed From The Perspective Of Islamic Religious Education - Maulana Iskandar (Yayasan Azhar Amanaa Yogyakarta, 2025)
Peace education is one of the important approaches in building a harmonious social life in the midst of a multicultural society. From the perspective of Islamic Religious Education (PAI), peace education is not only oriented towards conflict prevention, but also on instilling the values of justice, tolerance, equality, and respect for diversity. The implementation of these values can be seen through the Peace Village Program in Nglinggi Village, Klaten Regency, which was developed as an effort to build a community-based culture of peace. This research uses a qualitative approach with the type of library research. Data was obtained from various books, scientific journals, articles, and documents related to peace education, Islamic education, and the implementation of the Peace Village Program. The data collection technique was carried out through a documentation study and analyzed using a content analysis technique. The results of the study show that the implementation of the Peace Village Program in Nglinggi Village has reflected the five principles of peacebuilding in Islam, namely justice, equality, peace building, the search for peace, as well as pluralism and diversity. The values of justice and equality are realized through the Women Participation for Inclusive Society (WISE) program which focuses on economic empowerment and strengthening women's social participation. The value of peacebuilding is realized through the Community Early Warning Forum as a means of social dialogue and peaceful conflict resolution. The value of seeking peace is reflected in watching and learning together activities that aim to maintain unity and prevent social conflicts due to differences in political views. Meanwhile, the values of pluralism and diversity are realized through the Peace School program which instills an attitude of tolerance and respect for differences in religion, culture, and social backgrounds. The implementation of the Peace Village Program shows that community-based peace education has a strong relevance to the values of Islamic Religious Education in building a culture of peace, tolerance, and harmonious social life in a multicultural society.